Astronautics - Walter, Ulrich (Springer, 2019)
This textbook is about all basic physical aspects of spaceflight. Not all have been covered in the past editions. So, what is new in this third edition? First, there are new sections covering new topics, such as – Sections 1.2 and 1.3 dealing with the physics of a jet engine and general rocket performance have been widely extended to more sophisticated effects. – Sections 7.4.5 and 7.4.6 describe two general solutions to Newton’s gravitational equation of motion. – Section 7.7 studies stellar orbits, which are not subject to the standard but more general types of gravitational potentials. – Hypersonic flow theory for reentry vehicles is expounded in Sect. 6.2 as a basis to understand how lift and drag come about and in particular how both depend on the angle of attack, the most important control parameter to guide a winged body through the flight corridor (see Fig. 10.22). – Accordingly, the reentry of a Space Shuttle, which in this book even more serves as a case study, is explained in Sect. 10.7 in greater detail and in terms of NASA terminology. – In Sect. 8.1, the different basic types of orbit maneuvers are discussed and exemplified. – A new form of solution of Lambert’s problem is derived in Sect. 8.2.3, which is visualized in Fig. 8.8. – Section 8.4.3 discusses modern super-synchronous transfer orbits to GEO. – Relative motion in near-circular orbits is examined in Sect. 8.5.4. – The virial theorem for bounded and unbounded n-body systems is derived in Sect. 11.1.2 and used to discuss the stability of an n-body system. – Section 12.3 (Gravitational Perturbation Effects) has been revised and greatly extended including other and higher order perturbation terms. – Chapter 14 has been radically revised: There is a new Sect. 14.1 on orbit geometric issues (eclipse duration and access area) and a fully revised Sect. 14.2 on orbit determination.
The Physics of Space Flight